Natural enemies of armored scale (Hemiptera: Diaspididae) on avocado Hass in Michoacan, Mexico - LÁZARO-CASTELLANOS, CARLOS; GONZÁLEZ-HERNÁNDEZ, HÉCTOR; LOMELI-FLORES, J. REFUGIO; MYARTSEVA, SVETLANA N.; ORTEGA-ARENAS, LAURA D.; OCHOA-ASCENCIO, SALVADOR (Revista Colombiana de Entomología, 2012)
Natural enemies associated to armored scales on avocado Hass, and the percentage of parasitoidism on branches and fruits were recorded. The study was conducted on 14 avocado Hass orchards certified for exportation in the State of Michoacan, Mexico. From July 2009 to September 2010, armored scales and their entomophagous were collected in five orchards biweekly; meanwhile, in nine different orchards, levels of parasitoidism on armored scales were assessed bimonthly (from May to September 2010). The totals of scales species alive and parasitized scales per stage were recorded for each sample. The armored scales Hemiberlesia lataniae, Abgrallaspis aguacatae and Hemi- berlesia rapax were found infesting avocado leaves, branches and fruits. These armored scales were collected in ten, six, and two orchards respectively. The entomophagous insects recognized were Encarsia citrina present in 10 orchards and the most abundant with 108 specimens, Encarsia juanae in four orchards, 69 specimens collected, Plagiomerus nr. diaspidis four orchards, 65 specimens, Signiphora nr. borinquensis six orchards, 23 specimens, Marietta mexicana one orchard, five specimens, Aphytis sp. one orchard, two specimens and Chilocorus cacti two orchards, five specimens. The percentage of parasitoidism in armored scales infecting branches was bigger than in infested fruits; the number of parasitized scales increased between July and September 2010, possibly influenced by higher recorded temperatures and the relative humidity of the orchards. Encarsia citrina, which parasitizes the three armored scale species, has the best distribution and abundance, and it was present most of the year, therefore, it could be the parasitoid with better potential in management of armored scales.